Dekultrasi Bentuk Pertunjukan Musik Hadrroh - Alwan Hafiz; Hary Murcahyanto; Abdullah Muzakkar; Hulfatul Husna (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRAK This paper is based on the results of research that aims to describe the deculturation and form of Hadrroh musik performances in Gerisak Semanggleng Sakra Barat Village, Lombok Timur. This study used a qualitative descriptive method with a phenomenological approach. Collecting data by observation, interviews and documentation. From the results of the study, it is concluded that a result of the times and often following competitions the musik group has innovated to become a modern Hadrroh Modern musik group. To meet the needs of a show so as not to be outdated, this musik group underwent a change in the form of deculturation in the form of its performance by adding a keyboard musical instrument and presentation material using modern religious songs. The form of Hadrroh's musik shows is divided into two forms of performances, namely routine performances as a means of worship and non-routine performances (rituals) as entertainment. Keyword : Deculturation, Hadrroh Music, Performance Forms.